IMPLEMENTASI KOMUNIKASI PEMASARAN TERPADU PADA YAYASAN NURUL IBAD JAKARTA TIMUR - Ruzqiyah Ulfa; Rustono Farady Marta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Study about Integrated Marketing Communication or IMC has become a common issues. Not just profit-oriented institutions, non-profit institutions also need to know the communication strategy of the "new generation". The strategy in this integrated marketing communications that drive every aspect of the communication process to reach customers or the public with a message of unity in offering a benefit and ideas. Certainly not an easy thing when having a lot of media, ideas, activities and plans, but should have one "message" only. The integration process of marketing communication activities summarized simply by Chriss Fill (1995) through the integration of process models and marketing communication activities Hermawan Kertajaya in "3i Marketing Triangle" and "3² Values-Based Matrix". The Practice of marketing and social marketing products by Andreason, the emphasis is on the wider community that directly affect to the behavior and the needs or interests of the target as a basis. Yayasan Nurul Ibad as a non profit organization builds its brand image through their service by using marketing communication mix that consists of eight major communication model proposed by Philiph Kotler.Keywords: Integrated Marketing Communication, Message, Nurul Ibad